Tropoelastin: an in vivo imaging marker of dysfunctional matrix turnover during abdominal aortic dilation. Issue 5 (8th July 2019) - Lavin, Begoña; Lacerda, Sara; Andia, Marcelo E; Lorrio, Silvia; Bakewell, Robert; Smith, Alberto; Rashid, Imran; Botnar, René M; Phinikaridou, Alkystis
Abstract: Aims: Dysfunctional matrix turnover is present at sites of abdominal aortic aneurysm (AAA) and leads to the accumulation of monomeric tropoelastin rather than cross-linked elastin. We used a gadolinium-based tropoelastin-specific magnetic resonance contrast agent (Gd-TESMA) to test whether quantifying regional tropoelastin turnover correlates with aortic expansion in a murine model. The binding of Gd-TESMA to excised human AAA was also assessed. Methods and results: We utilized the angiotensin II (Ang II)-infused apolipoprotein E gene knockout (ApoE −/− ) murine model of aortic dilation and performed in vivo imaging of tropoelastin by administering Gd-TESMA followed by late gadolinium enhancement (LGE) magnetic resonance imaging (MRI) and T1 mapping at 3 T, with subsequent ex vivo validation. In a cross-sectional study ( n  = 66; control = 11, infused = 55) we found that Gd-TESMA enhanced MRI was elevated and confined to dilated aortic segments (control: LGE =0.13 ± 0.04 mm 2, control R1 = 1.1 ± 0.05 s −1 vs. dilated LGE =1.0 ± 0.4 mm 2, dilated R1 =2.4 ± 0.9 s −1 ) and was greater in segments with medium (8.0 ± 3.8 mm 3 ) and large (10.4 ± 4.1 mm 3 ) compared to small (3.6 ± 2.1 mm 3 ) vessel volume. Furthermore, a proof-of-principle longitudinal study ( n  = 19) using Gd-TESMA enhanced MRI demonstrated a greater proportion of tropoelastin: elastin expression in dilating compared to non-dilating aortas, which correlated with the rate of aortic expansion. Treatment with pravastatin and aspirin ( n  = 10) did not reduce tropoelastin turnover (0.87 ± 0.3 mm 2 vs. 1.0 ± 0.44 mm 2 ) or aortic dilation (4.86 ± 2.44 mm 3 vs. 4.0 ± 3.6 mm 3 ). Importantly, Gd-TESMA-enhanced MRI identified accumulation of tropoelastin in excised human aneurysmal tissue ( n  = 4), which was confirmed histologically. Conclusion: Tropoelastin MRI identifies dysfunctional matrix remodelling that is specifically expressed in regions of aortic aneurysm or dissection and correlates with the development and rate of aortic expansion. Thus, it may provide an additive imaging marker to the serial assessment of luminal diameter for surveillance of patients at risk of or with established aortopathy. Graphical Abstract: